Association of Breakfast Habits and Nutritional Status with Dysmenorrhea Among Adolescent Girls in SMAN 8 Surabaya - Anisa Farasani; Taufiqurrahman; Nuning Marina Pengge; Nurul Hindaryani (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Dysmenorrhea is a common condition among adolescent girls, often linked to poor nutritional status and breakfast skipping. Despite its high prevalence and impact on academic performance, studies exploring its association with lifestyle factors in Indonesian high school students remain limited. This study aims to analyze the association between breakfast habits and nutritional status with the incidence of dysmenorrhea among adolescent girls at SMAN 8 Surabaya. This study used a cross-sectional design involving 68 female students selected through proportional random sampling. Data were collected using anthropometric measurements, a validated FFQ for breakfast habits, and a dysmenorrhea questionnaire, then analyzed using Spearman correlation with a significance level of p < 0.05. The majority of respondents were 17 years old and reported experiencing mild dysmenorrhea. The majority had normal nutritional status but rarely ate breakfast. Spearman test showed no significant relationship between breakfast habits and dysmenorrhea (p = 0.948), while nutritional status showed a significant relationship with dysmenorrhea (p = 0.004).